Explaining positive deviance in public sector reforms in development - Andrews, Matt (World Institute for Development Economic Research (UNU-WIDER), 2013)
Public sector reforms are commonplace in developing countries. Much of the literature about these reforms reflects on their failures. This p aper asks about the successes and investigates which of two competing theories best explain why some reforms exhibi
Keywords: Development; Innovation; Reform; case survey; governance; growth; leadership